A Naturalist Ontology of Instantiation. (22nd August 2017) - Cumpa, Javier
Abstract: The aim of this paper is to defend a naturalistic approach to instantiation and the Principle of Instantiation. I argue that the instantiation of an ordinary property F consists of two coordinated relationships at the levels of the manifest and scientific images, namely, constituency and entailment. Also, I offer an account of the Principle of Instantiation related to this conception of instantiation based on the notion of scientific prediction.